1974
DOI: 10.1161/01.cir.49.1.13
|View full text |Cite
|
Sign up to set email alerts
|

Chagasic Cardiopathy

Abstract: SUMMARYTwenty-four out of 25 patients with Chagas' heart disease have circulating immunoglobulins which react by indirect immunofluorescence technique with endocardium, interstitium and blood vessels of the heart. With skeletal muscle the reaction was observed in interstitium and vascular structures, but with other organs it was limited to vascular structures. This endocardial-vascularinterstitial factor (EVI) fixed complement. Some evidence indicated that this reaction could be obtained using the serum and ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0

Year Published

1983
1983
2005
2005

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…sensitivity responses toward a tissue-specific heart component bearing structural similarities to a given T. cruzi antigen. Several investigators found autoantibody and self-reactive T-cell formation in human and experimental T cruzi infection (5,6). Crossreactive autoantibodies were mainly directed toward ubiquitous and evolutionarily conserved molecules (7,8).…”
mentioning
confidence: 99%
“…sensitivity responses toward a tissue-specific heart component bearing structural similarities to a given T. cruzi antigen. Several investigators found autoantibody and self-reactive T-cell formation in human and experimental T cruzi infection (5,6). Crossreactive autoantibodies were mainly directed toward ubiquitous and evolutionarily conserved molecules (7,8).…”
mentioning
confidence: 99%
“…Sera from patients suffering from both forms of the disease demonstrate cross-reactivity with the parasite as well as with normal endocardium, blood vessels, and material surrounding striated muscle and Schwann cells [25]. It was further recognized that these sera as well as sera from primates infected with Trypanosoma cruzi reacted specifically with basement membranes, as can be seen in Fig.…”
Section: Chagas Diseasementioning
confidence: 83%
“…Autoreactive antibodies and T cells directed to target organs have been described in experimental and natural chronic T. cruzi infection (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14). There are at least two nonexclusive explanations for the generation of autoimmunity in Chagas disease: (i) infection with the parasite perturbs immunoregulation, leading to loss of tolerance for self-antigens; (ii) immune recognition of T. cruzi antigens is crossreactive with selected mammalian antigens, leading to autoimmunity (molecular mimicry).…”
mentioning
confidence: 99%
“…Antibodies to endocardium, vasculature, and interstitium of striated muscle (EVI) and Schwann cells ofperipheral nerve have been found in acute and chronic cases of Chagas disease (3,4). Antibodies to EVI have been found to be directed to carbohydrate on mammalian laminin, apparently stimulated by crossreactive carbohydrate epitopes present in T. cruzi (5,6).…”
mentioning
confidence: 99%